(untitled) (Research, Society and Development, 2021)
Caramel coloring has been widely used in foods and beverages and is globally regulated as a chemical additive. The four distinct classes of caramel dye (simple caramel (I), sulfite caramel (II), ammonia caramel (III) and sulfite-ammonia caramel (IV)) are well characterized and each has specificities that vary with the types of processing of the compound, especially the addition of reagents that can give rise to low molecular weight compounds, such as 4-methylimidazole, a by-product of caramel IV, which can have a significant toxicological effect. In view of the high consumption of processed foods and the potential long-term exposure of this compound, in different age groups, the aim of this review was to summarize the most relevant studies available in the last 5 years on the toxic effects of 4-methylimidazole, in the bases PubMed, Science Direct, and Lilacs databases. The results of the evaluated studies are divergent and the mechanisms of toxicity are not well elucidated, although some studies have found negative health effects with exposure to 4-methylimidazole, making further studies relevant to clarify its real safety.